Intellectual property protection and the formation of entrepreneurial growth aspirations - Autio, Erkko; Acs, Zoltan (Strategic Entrepreneurship Journal, 2010)
Abstract Applying real options logic, we build and test a multilevel model that explicates the influence of a country's intellectual property protection regime on the effect of an individual's human and financial capital on entrepreneurial growth aspirations. The results suggest that the strength of the intellectual property regime moderates negatively the relationship between an individual's education and entrepreneurial growth aspirations; and it moderates positively the relationship between an individual's household income and growth aspirations. Intellectual property protection, thereby, encourages specialization amongst differently qualified entrepreneurs. Our findings support claims that strategic entrepreneurial behaviors cannot be fully understood without giving attention to the context in which those behaviors are observed. Copyright © 2010 Strategic Management Society.